2013
DOI: 10.1002/jcph.186
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic and pharmacodynamic modeling of different formulations of ONO‐5334, cathepsin K inhibitor, in Caucasian and Japanese postmenopausal females

Abstract: ONO-5334, a selective inhibitor of cathepsin K, is a potential new treatment for osteoporosis. The objectives of this study were to (1) develop population pharmacokinetic-pharmacodynamic (PK-PD) models for ONO-5334 using dose-ascending data from healthy postmenopausal females, (2) examine comparability of PK and/or PD profile between Caucasian and Japanese, and (3) compare PK-PD profile between immediate release tablet (IRT) and sustained release tablet (SRT). The population PK-PD models were developed for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…A population PK model simultaneously analyzing both ONO‐5334 IRT and SRT data was developed using intensive PK sampling collected in 4 phase 1 studies (protocol numbers: ONO‐5334POE001, ONO‐5334‐01, ONO‐5334POE006, and ONO‐5334‐02) and a study where only trough levels were collected (phase 2 OCEAN study). Design details for the phase 1 studies can be found elsewhere . In the OCEAN study, a total of 285 subjects (57 per treatment group) were randomized to receive placebo, alendronate 70 mg once weekly (QW) or 1 of 3 regimens of ONO‐5334 50 mg BID, 100 mg QD, or 300 mg QD, for 12 months.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A population PK model simultaneously analyzing both ONO‐5334 IRT and SRT data was developed using intensive PK sampling collected in 4 phase 1 studies (protocol numbers: ONO‐5334POE001, ONO‐5334‐01, ONO‐5334POE006, and ONO‐5334‐02) and a study where only trough levels were collected (phase 2 OCEAN study). Design details for the phase 1 studies can be found elsewhere . In the OCEAN study, a total of 285 subjects (57 per treatment group) were randomized to receive placebo, alendronate 70 mg once weekly (QW) or 1 of 3 regimens of ONO‐5334 50 mg BID, 100 mg QD, or 300 mg QD, for 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…The intra‐ and inter‐assay precision was less than 15% (coefficient of variation), and the intra‐ and inter‐assay accuracy was within 15% of the nominal values for ONO‐5334. The detail of the analytic method can be found elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations